Adoption of agile methodology for improving IT project performance - Rajan, Eldho Roshan; Santhosh, Vijayakumar Ambujakumari (Serbian Journal of Management, 2021)
Most of the IT organizations are facing various challenges such as technological advancement, new customer requirements, merger & acquisition, and changing market demands, which should be addressed to survive in the industry. For enhancing more value to the customer in the project, the best option is to choose Agile Methodology for managing the project, which helps to accommodate the ad-hoc business requirement than pre-planned. Though, most of the organization, especially in the IT industry is shifting to Agile methodology practice, which helps to enjoy the benefit of better collaboration and customer experience. The study was conducted among 404 IT professionals from the IT corridors of India to understand the influence of Agile methodology on IT project performance. Most responses received from people who have sound experience in IT project management which assures the quality of results obtained. From study, it has been found that Agile methodology (β= 0.630, p<0.00) has a significant and positive impact on the project performance. Also, the study proves that people who are working in Scrum framework (Agile methodology) improves the project quality as well as business value. Based on Stepwise regression results, Product ownership has higher degree of importance than other independent variable for the individual work performance which solidifies the requirement for software development. Multicollinearity Assessment shows Product Ownership and Development Practice have more impact on project performance than Team considered for the study. Previous studies didn’t cover the aspect as well as areas proposed in this study to arrive the conclusion of Scrum framework for project performance, and it opens the pathway for future research work.